Unsteady Flow to Viscous Thin Films on a Vertical Surface - Khidr Khidr; Hanin Jasim; Hikmat Mustafa (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper we have investigated the unsteady flow to thin films of an incompressible liquids with no inertia force, continuity equation and Nervier-Stokes equations are used to obtain the equation that governs this type of flow, this equation is solved analytically to find the thickness of the film.